World Catalogue of the Druid Flies (Diptera: Schizophora: Clusiidae) - Lonsdale, Owen (Zootaxa, 2017)
Family-, genus- and species-level groups in the family Clusiidae (Diptera: Schizophora) are catalogued, providing reference to occurrences of these taxa in the literature, including all those relevant to nomenclature. Full synonymies are provided, including generic combinations for species, and the collection locality, depository and sex of primary type specimens. Published species distributions are provided, noting country and biogeographic region; specimen data representing new country records for species are listed. The Clusiidae are known from 636 species in 14 genera and three subfamilies, with many additional species expected. Nearly half of all described species are Sobarocephala, with 269 species, followed by the clusiodine genera Heteromeringia (86 species), Allometopon (68), Hendelia (53 species), Czernyola (50 species) and Clusiodes (31 species); the remaining eight genera (seven extant, one fossil) are smaller, consisting of 1 to 16 species. Two other fossil genera, Acartophthalmites Hennig and Xenanthomyza Hennig, are also treated here, but are unlikely to belong to the family. Taxa formerly considered Clusiidae are listed. Tranomeringia scutellata Sasakawa is transferred to Heteromeringia, n. comb. Czernyola is maintained as the replacement name for Craspedochaeta, following Bezzi (1907), McAlpine (1971) and Lonsdale, et al. (2010), resulting in the following new combinations: Czernyola amazonensis (Lonsdale & Marshall) n. comb.; C. apsilutea (Lonsdale & Marshall) n. comb.; C. argoniae (Lonsdale & Marshall) n. comb.; C. biloba (Lonsdale & Marshall) n. comb.; C. brunneivibrissa (Lonsdale & Marshall) n. comb.; C. candida (Lonsdale & Marshall) n. comb.; C. chauliodon (Lonsdale & Marshall) n. comb.; C. chela (Lonsdale & Marshall) n. comb.; C. concinna (Williston) n. comb.; C. feminea (Lonsdale & Marshall) n. comb.; C. loreto (Lonsdale & Marshall) n. comb.; C. maai (Sasakawa) n. comb.; C. melanosoma (Lonsdale & Marshall) n. comb.; C. novaeguinea (Soós) n. comb.; C. pacaraima (Lonsdale & Marshall) n. comb.; C. parva (Sasakawa) n. comb.; C. phaios (Lonsdale & Marshall) n. comb.; C. pilosa (Sasakawa) n. comb.; C. pleuralis (Williston) n. comb.; C. pollostos (Lonsdale & Marshall) n. comb.; C. protomis (Lonsdale & Marshall) n. comb.; C. quinquespinula (Sasakawa) n. comb.; C. sasakawai (Lonsdale & Marshall) n. comb.; C. spinulifera (Sasakawa) n. comb.; C. unguicauda (Sasakawa) n. comb.; C. varicolor (Sueyoshi) n. comb.; C. vietnamensis (Sasakawa) n. comb.; C. weemsi (Lonsdale & Marshall) n. comb.; C. xanthonotum (Lonsdale & Marshall) n. comb.; C. xanthopleura (Sasakawa) n. comb.; C. zongo (Lonsdale & Marshall) n. comb.